Analisis Proses Perubahan APBDesa Dalam Rangka Prioritas Penggunaan Dana Desa Di Masa Pandemi Covid-19 - I Gede Made Artha Dharmakarja; I Gede Komang Chahya Bayu Anta Kusuma; Salsabila Nur Azizah; Willy Rifokto Kesuma (PT WIM Solusi Prima, 2022)
The Government of Indonesia is utilizing the distribution of village funds which are transferred annually to all villages to overcome the covid-19 pandemic in 2020. This study aims to determine the ability of village governments to adapt to managing village finances by analyzing the village budget amandment. This study uses a descriptive qualitative method by analyzing primary data in the form of transcripts from interviews with financial managers in Kalirong and Kedungturi Village as well as secondary data in the form of APBDesa before and after the amandment. The analysis uses the theory of participation, effectiveness and AGIL to explain the dynamics of the APBDesa amandment process. The results of the study show that even though the mechanism for drafting the amandment to the APBDesa does not fully follow the applicable regulatory procedures amid social restrictions, its management is able to achieve the goal of overcoming the impact of the covid-19 pandemic in an accountable manner. This research is expected to be able to show the conditions of village resilience in order to strengthen government policies in the context of empowerment and development through village fund transfers. Pemerintah Indonesia memanfaatkan penyaluran dana desa yang setiap tahun ditransfer ke seluruh desa untuk mengatasi pandemi covid-19 di tahun 2020. Penelitian ini bertujuan untuk mengetahui kemampuan pemerintah desa dalam beradaptasi mengelola keuangan desa dengan menganalisis perubahan APBDesa. Penelitian ini menggunakan metode kualitatif deskriptif dengan menganalisis data primer berupa transkrip hasil wawancara pengelola keuangan di Desa Kalirong dan Desa Kedungturi serta data sekunder berupa APBDesa sebelum dan sesudah perubahan. Analisis menggunakan pendekatan teori partisipasi, efektivitas dan AGIL untuk menjelaskan dinamika proses perubahan APBDesa. Hasil penelitian menunjukkan bahwa meskipun mekanisme penyusunan perubahan APBDesa tidak sepenuhnya mengikuti prosedur ketentuan yang berlaku di tengah pembatasan sosial namun pengelolaannya mampu mewujudkan tujuan untuk mengatasi dampak pandemi covid-19 secara akuntabel. Penelitian ini diharapkan mampu menunjukkan kondisi ketahanan desa guna memperkuat kebijakan pemerintah dalam rangka pemberdayaan dan pembangunan melalui transfer dana desa.